2020
DOI: 10.1097/md.0000000000019587
|View full text |Cite
|
Sign up to set email alerts
|

A case report of cryptococcal meningitis associated with ruxolitinib

Abstract: We herein report a 76-year-old Japanese man with myelofibrosis who developed cryptococcal meningitis. After treatment for 5 months with ruxolitinib, the patient presented with fever and disturbance of consciousness. Marked nuchal stiffness was noted. The magnetic resonance imaging results of the brain were normal. Lumbar puncture showed an opening cerebrospinal fluid (CSF) pressure of 110 mm H2O, pleocytosis (85 mononuclear cells and 222 polymorphonuclear cells/μL), decreased CSF/serum glucose ratio (43%), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…From those results, the most common opportunistic pathogens that benefit from these immune defects include bacteria, mycobacteria, viruses, and fungi, similar to those seen in human immunodeficiency virus (HIV)-related infections. The causative pathogens in previously reported cases of ruxolitinib-associated infections are summarized in Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Consistent with the foregoing, it appears that Cryptococcus and nontuberculous mycobacteria were able to simultaneously infect our patient due to the downregulation of multiple cytokines.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…From those results, the most common opportunistic pathogens that benefit from these immune defects include bacteria, mycobacteria, viruses, and fungi, similar to those seen in human immunodeficiency virus (HIV)-related infections. The causative pathogens in previously reported cases of ruxolitinib-associated infections are summarized in Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Consistent with the foregoing, it appears that Cryptococcus and nontuberculous mycobacteria were able to simultaneously infect our patient due to the downregulation of multiple cytokines.…”
Section: Discussionsupporting
confidence: 84%
“…From previous case reports of cryptococcal infection, which are summarized in Table 2 [ 4 6 , 9 11 ], 6 patients with a history of ruxolitinib treatment developed cryptococcal infection. Wysham NG, et al [ 4 ] and Hirano A, et al [ 5 ] reported 2 cases of pulmonary cryptococcosis, but the other four cases presented as fungemia, pericardial involvement, and meningitis or meningoencephalitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptococcosis: pneumonia and pulmonary infection [ 246 – 248 ], meningoencephalitis [ 249 ], meningitis [ 250 ]…”
Section: Immunosuppressive Therapy As a Risk Factor For Opportunistic Infectionmentioning
confidence: 99%
“…However, the inhibition of the JAK-signal transducer and activator of transcription (STAT) pathway may lead to the dysfunction of cellular immunity (5), which results in decreased production of several proinflammatory cytokines (4,(6)(7)(8)(9)(10). Consequently, various opportunistic infections related to ruxolitinib treatment have been reported previously (4,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%